Tax avoidance provisions of the South African Income Tax Act - Ndema, Yondela (Department of Commercial Law, 2021)
My thesis is on tax avoidance provisions in South Africa. I want to present an overview of tax avoidance in South Africa but I will concentrate more on section 103(1) which is the general anti - tax avoidance provision in South Africa.I will then proceed to look at the artificial tax avoidance, and a comparative analysis between United Kingdom (UK) and South Africa on the substance over form approach as a new approach to tax avoidance. Much has been said on tax avoidance and it is an area which has generated much interest and curiosity to the society at large.